2018
DOI: 10.1055/s-0038-1624579
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Perforation due to Deep Infiltrating Endometriosis during Pregnancy: Case Report

Abstract: We report the case of a 33 year-old woman who complained of severe dysmenorrhea since menarche. From 2003 to 2009, she underwent 4 laparoscopies for the treatment of pain associated with endometriosis. After all four interventions, the pain recurred despite the use of gonadotropin-releasing hormone (GnRH) analogues and the insertion of a levonorgestrel intrauterine system (LNG-IUS). Finally, a colonoscopy performed in 2010 revealed rectosigmoid stenosis probably due to extrinsic compression. The patient was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
(49 reference statements)
0
2
0
4
Order By: Relevance
“…Setúbal et al reported on three cases of bowel perforation due to endometriosis, at their own center, as well as 12 cases through a search of the literature until 2013 [79]. A further three cases of spontaneous bowel perforation during pregnancy in endometriosis patients were reported in 2014 [80], 2016 [81], and 2018 [82]. All cases had the diagnosis proven either prior to pregnancy or through biopsies taken during surgery.…”
Section: Spontaneous Bowel Perforation In Pregnancymentioning
confidence: 99%
“…Setúbal et al reported on three cases of bowel perforation due to endometriosis, at their own center, as well as 12 cases through a search of the literature until 2013 [79]. A further three cases of spontaneous bowel perforation during pregnancy in endometriosis patients were reported in 2014 [80], 2016 [81], and 2018 [82]. All cases had the diagnosis proven either prior to pregnancy or through biopsies taken during surgery.…”
Section: Spontaneous Bowel Perforation In Pregnancymentioning
confidence: 99%
“…Por isso, na maioria dos casos só é possível diagnosticar através de exames de imagem, como ultrassonografia transvaginal (USTV), ultrassonografia No que se refere a EIP, é de suma importância a avaliação intestinal, uma vez que o envolvimento nessa área pode ser multifocal, podendo comprometer cólon, retossigmoide, o apêndice, o ceco e o íleo distal. O número de lesões e a profundidade delas estão relacionados no que tange a avaliação e o prognóstico do tratamento cirúrgico (CARNEIRO MM, et al, 2018). Em presença de indícios e sintomas de Endometriose Infiltrativa Profunda ou quando os testes revelam a presença de um endometrioma, é aconselhável procurar uma consulta com um ginecologista para realização de exames de imagens mais minuciosos, como Ressonância Magnética Pélvica ou Ecografia Transvaginal dinâmica.…”
Section: Revisão Bibliográficaunclassified
“…A endometriose pode ser caracterizada como uma condição de crescimento celular progressivo, benigna, de dependência estrogênica e crescimento endotelial (CARNEIRO MM, et al, 2018). Tendo uma prevalência estimada em todo o mundo de 176 milhões de mulheres acometidas (ZONDERVAN KT, et al, 2018).…”
Section: Introductionunclassified
“…Affecting the appendix***, 26 terminal ileum***, 27 and colon***, 28 causing tissue perforation with severe gastrointestinal bleeding 29 or urohaemoperitoneum*** with urinary tract endometriosis 30 Involution of decidualised (progesterone mediated*) endometriotic implants associated with parametrial veins causing vascular fragility and spontaneous peritoneal bleeding*** 31 Uterine rupture*** 32,33 in nulliparous women both before and during labour or uterine scar weakness following excision of rectovaginal nodule 34 or electrosurgical treatment 23 such cases, 61% occur antenatally in the third trimester, 18% intrapartum, and 21% up to 42 days postpartum. 38 A review of 21 studies 31 showed that 72% were nulliparous presenting with sudden onset of nonspecific abdominal pain (95%) and signs of hypovolemic shock (70%).…”
Section: Endometriotic Decidualised Implant Invasionmentioning
confidence: 99%